2009
DOI: 10.1007/s00421-009-1141-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent hypoxia on hematological parameters after recombinant human erythropoietin administration

Abstract: Recent publications reflect the anti-doping authorities' concern about the use of altitude simulator systems as violating the spirit of sport criterion (Levine 2006; Loland and Murray 2007; Spriggs 2005). The aim of our study was to determine whether intermittent hypoxic treatments could modify the hemoglobin, hematocrit, reticulocytes, and erythropoietic stimulation index (OFF-Hr Score) values after administration of rHuEPO-alpha. Although these hematological parameters are of secondary nature some internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Additionally, other factors, such as simulated altitude, altitude simulation technology, hypoxia exposure time per session and the program duration, can influence the athletes' final response (22). Moreover, the different athletes' responses to IHT are most likely related to genetic factors (9), and in some cases, the effects are similar to those obtained by administration of exogenous erythropoietin (25).…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, other factors, such as simulated altitude, altitude simulation technology, hypoxia exposure time per session and the program duration, can influence the athletes' final response (22). Moreover, the different athletes' responses to IHT are most likely related to genetic factors (9), and in some cases, the effects are similar to those obtained by administration of exogenous erythropoietin (25).…”
Section: Discussionmentioning
confidence: 66%
“…Accordingly, also the alveolar partial pressure of oxygen after respiratory muscle training significantly increased by approximately 10% (Esposito et al 2010). In another article published in this journal by Sanchis-Gomar et al (2009), it was previously shown that intermittent hypoxic treatment is at least as effective as the administration of recombinant human erythropoietin to increase the red blood cell mass and, inherently, the aerobic performances, in agreement with the previous findings of Mackenzie et al (2008). Taken together, these data support the hypothesis that normobaric hypoxia might indeed contribute to improving sports performance.…”
mentioning
confidence: 94%
“…After 23 days, rHuEPO administration, normoxic animals showed a 45% decrease in their hemoglobin concentration when compared with the animals that underwent a 12-h period of hypoxia daily. Likewise, the normoxic animals showed a 35% decrease in their hematocrit concentration when compared with the animals that underwent 12-h periods of hypoxia daily (Sanchis-Gomar et al 2009). Although this experiment was carried on in mice, similar Wndings were previously observed in humans (Heinicke et al 2003).…”
mentioning
confidence: 95%
“…We read with interest the article of Sanchis-Gomar et al (2009) on the eVect of intermittent hypoxia on hematological parameters after recombinant human erythropoietin (rHuEpo) administration. The Wndings of this valuable study further highlight the fuzzy boundary existing between what is licit and what is not in sports.…”
mentioning
confidence: 98%